Women Empowerment through Self-Help Groups: A Study in Jalukie Block, Peren District of Nagaland - Isapeule; Longkumer, J.; Longchar, T. (International Journal of Bio-resource and Stress Management, 2018)
SHGs were started in Nagaland during 1999-2000 under the centrally sponsored scheme SGSY (Mishra and Langwangbe, 2014). Besides SGSY, the state Rural Development Department, Department of Women Development, North East Rural Livelihoods Project (NERLP), and Nagaland Empowerment of People through Economic Development (NEPeD) has also played a great role in promoting SHGs in the state. NGOs like Rongmai Baptist Association Nagaland (RBAN), Prodigals’ Home, Development Association of Nagaland (DAN) and Agency for Integral Development Action (AIDA) played a significant role in promotion of women empowerment through formation of SHGs in various areas of the state. The study was undertaken in Jalukie block, Peren district of Nagaland. Findings revealed that higher incidence was observed from SHG members in the sample consisted of young aged women up to 35 years (47.50%), educational qualification up to secondary standard (82.50%), nuclear family type (85.00%), family size of 3-5 members (43.33%), business occupation (58.33%), annual average income of above ` 26,784–` 49,316/- (58.33%), high level of self-confidence (67.50%), and having a family support to great extent (63.33%). Observations depicted that the SHG members were involved in small scale business enterprises such as piggery, weaving, poultry, grocery shops and vegetables. The analysis showed that 65.83% of SHG members were empowered moderately, while 17.50% were empowered at low level and about 16.67% were highly empowered. The study showed that Self Help Groups can contribute towards empowerment of women and can play a very important role in bringing about positive changes in their lives.